The Effect of Delayed Oncology Surgery on Survival Outcomes for Patients With Gastric Cancer During the COVID-19 Pandemic: Evidence-Based Strategies - Ma, Jichun; Zhu, Chenglou; Li, Weidong; Qiu, Zhisheng; Yang, Jian; Ge, Long; Da, Mingxu (Frontiers in Oncology, 2022)
Objective To evaluate the impact of delay the gastrectomy on gastric caner patients survival outcomes during the COVID-19 pandemic. Methods Databases including PubMed, MEDLINE (using the Ovid platform), Embase, the Cochrane Library, COVID-19 Open Research Dataset Challenge, COVID-19 Research Database (WHO), ClinicalTrials.gov, WHO International Clinical Trials Registry Platform were searched for studies of any design and in any setting that included patients with gastric cancer from their inception to July 31, 2021. Hazard ratio (HR) and 95% confidence intervals (CI) of research endpoints in each study were calculated. Statistical analyses were performed with Stata 12.0 Results A total of 8 studies involving 4052 gastric cancer patients were eligible and included in present meta-analysis. The result of meta-analysis was shown that delaying surgery for less than 8 weeks may not decrease OS(HR=0.91, 95%CI: 0.80~1.04, P=0.167) and DFS(HR=0.96, 95%CI: 0.62~1.50, P=0.872) in gastric cancer. Our meta-analysis also illustrated that delay in surgery more than 4 weeks(HR=0.85, 95%CI: 0.56~1.27, P=0.421), 6 weeks(HR=0.88, 95%CI: 0.61~1.27, P=0.490), 8 weeks(HR=0.93, 95%CI: 0.80~1.07, P=0.314) also was not associated with a decrease OS. Conclusion A delay in surgery of less than 8 weeks is not associated with worse overall survival for patients with gastric cancer.